2020
DOI: 10.1002/jaoc.12074
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Experimental Single‐Subject Design: Comparing Seeking Safety and Canine‐Assisted Therapy Interventions Among Mentally Ill Female Inmates

Abstract: This repeated measures quasi‐experimental study evaluated the effectiveness of 2 interventions, Seeking Safety and canine‐assisted therapy, with female prisoners with trauma histories on a mental health unit. Results indicate both are effective at reducing anxiety, depression, and posttraumatic stress disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…In this category, we included studies with experimental conditions that specified physical contact with an animal, such as petting, as the factor in their intervention (e.g., Crump and Derting, 2015 ; Holman et al, 2020 ; Binfet et al, 2022 ). We found that 12.79% ( n = 22) of the studies controlled for physical contact as a specific factor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this category, we included studies with experimental conditions that specified physical contact with an animal, such as petting, as the factor in their intervention (e.g., Crump and Derting, 2015 ; Holman et al, 2020 ; Binfet et al, 2022 ). We found that 12.79% ( n = 22) of the studies controlled for physical contact as a specific factor.…”
Section: Resultsmentioning
confidence: 99%
“…In this category, we included studies with control conditions that had a therapeutic component, such as trauma-focused therapy (e.g., Allen et al, 2021 ), psychological treatment (e.g., Muela et al, 2017 ; Holman et al, 2020 ), or physiotherapeutic treatment (e.g., Beinotti et al, 2013 ; Rodrigo-Claverol et al, 2020 ). In total, 37.21% ( n = 64) of the analyzed studies controlled for therapeutic aspects as a non-specific factor.…”
Section: Resultsmentioning
confidence: 99%